TASKS FOR INDEPENDENT STUDY COMPONENT OF SCIENTIFIC CONTENT IN COMPOSITION - Sh. Abdurahmanov; M. Mirzaabdullaev; D. Tursunalieva (American Journals, 2023)
The scientific article investigates the task of providing a component of the scientific content of the task of independent education on the topic of “Conjugation" in the academic discipline engineering graphics.
Keywords: didactic principles, the scientific principle, independent education, the task of independent education, engineering graphics, the theme of